Phosphodiesterase 10 inhibitors in clinical development for CNS disorders. (3rd June 2017) - Geerts, Hugo; Spiros, Athan; Roberts, Patrick
ABSTRACT: Introduction : Phosphodiesterase 10 inhibitors (PDE10-I), are conceptually attractive drugs with a potential great therapeutic window as their enriched striatal localization may likely stimulate D1 R and reduce D2 R downstream effects. However, so far selective PDE10-I with efficacy in animal models have not shown benefit in clinical trials and unexpectedly revealed a substantial dyskinesia motor side-effect. Areas covered : This paper reviews the underlying biological rationale of PDE10 as a target in schizophrenia, Parkinson's and Huntington's disease based on peer-reviewed published articles, the status of the different PDE10–I in clinical development for various CNS indications and explores possible reasons for the clinical trial failures and translational disconnect. Expert commentary : Possible explanations include non-optimal dose and titration schedule, but more importantly the differential non-linear pharmacodynamic interactions with individual comedications, the species difference in underlying neurobiology and the differences with the rich pharmacology of successful antipsychotics. The authors also present optogenetics, DREADD (Designer Receptor Exclusively Activated by Designer Drug) technology, organoids based on iPSC (induced Pluripotent Stem Cells) and advanced computer modeling and simulation as possible new technologies to further elucidate the complex nature of the emergent properties of key neuronal circuits that drive human behavior.